2012
DOI: 10.1007/s00348-012-1272-x
|View full text |Cite
|
Sign up to set email alerts
|

A multiphase shock tube for shock wave interactions with dense particle fields

Abstract: Currently there is a substantial lack of data for interactions of shock waves with particle fields having volume fractions residing between the dilute and granular regimes. To close this gap, a novel multiphase shock tube has been constructed to drive a planar shock wave into a dense gas-solid field of particles. A nearly spatially isotropic field of particles is generated in the test section by a gravity-fed method that results in a spanwise curtain of spherical 100-micron particles having a volume fraction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
91
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(93 citation statements)
references
References 19 publications
2
91
0
Order By: Relevance
“…In particular, they have shown that for dense particle clouds, important effects to account for during the shock interaction include the two-way coupling between the particles and gas, the particle inertia, and unsteady forces. When a planar shock wave interacts with a planar particle layer within a shock tube, the thickness of the particle layer increases in the longitudinal direction, whereas the layer surfaces remain relatively stable in the transverse direction [16,17]. In contrast, systems involving the interaction between a decaying blast wave and a cylindrical or spherical particle layer are more susceptible to the generation of instabilities at the surfaces of the particle layer.…”
Section: Overviewmentioning
confidence: 92%
See 1 more Smart Citation
“…In particular, they have shown that for dense particle clouds, important effects to account for during the shock interaction include the two-way coupling between the particles and gas, the particle inertia, and unsteady forces. When a planar shock wave interacts with a planar particle layer within a shock tube, the thickness of the particle layer increases in the longitudinal direction, whereas the layer surfaces remain relatively stable in the transverse direction [16,17]. In contrast, systems involving the interaction between a decaying blast wave and a cylindrical or spherical particle layer are more susceptible to the generation of instabilities at the surfaces of the particle layer.…”
Section: Overviewmentioning
confidence: 92%
“…Particle jets are formed as the fragments move radially outwards, and shed particulate in their wakes (d). Figure adapted from Loiseau et al [18] Recent experiments by Wagner et al [16] within a multiphase shock tube have provided a well-characterized dataset for the validation of the physical processes that occur during the shock interaction with a dense array of particles in air. Ling et al [17] have demonstrated that the processes associated with the shock interaction with a dense particle curtain differ significantly from those in a dilute gas-particle mixture.…”
Section: Overviewmentioning
confidence: 99%
“…There has been success in modeling these flows when the solid phase is in either the di-5 lute (Drew, 1983;Magnaudet and Eames, 2000;Crowe et al, 2012) or densely packed (Baer and Nunziato, 1986;Powers et al, 1990) regimes. However, the modeling of compressible flows when the solid phase has a volume fraction between these extremes has lagged behind (Wagner et al, 2012). Additionally, this intermediate regime of multiphase flows has seen relatively little experi-10 mental investigation due to the difficulties in isolating and measuring the high solid volume fraction regions.…”
Section: Introductionmentioning
confidence: 97%
“…A recent experiment has been developed that successfully isolates this multiphase flow regime by investigating the interaction between a shock wave and a dense non-compacted particle curtain (Wagner et al, 2012). The particle cur-15 tain used in this experiment is generated by the granular flow of glass beads through a hopper with a slit opening.…”
Section: Introductionmentioning
confidence: 99%
“…Examples include shock tubes for the study of non-equilibrium vapour condensation (Maerefat et al 1989), droplet condensation in expansion tubes (Peters and Rodemann 1998) and studies of particle-dense flow fields (Wagner et al 2012).…”
Section: Introductionmentioning
confidence: 99%